Laparoendoscopic single-site cholecystectomy: A randomized controlled study. Issue 2 (March 2012) - Zheng, Mingwei; Qin, Mingfang; Zhao, Hongzhi
Abstract: This study reports the initial experience with laparoendoscopic single-site (LESS) cholecystectomy and compares it withl aparoscopic cholecystectomy (LC) through a randomized controlled trial. Sixty selective patients diagnosed with cholelithiasis or polyp lesion of the gallbladder (PLG) were randomly divided into two groups undergoing either LESS cholecystectomy or LC separately. The clinical data about operations and recovery of the two groups were compared. In the LESS group 28 of 30 patients underwent LESS cholecystectomy successfully and the remaining two (6.7%) were converted to standard laparoscopic surgery. LC was successfully performed in all patients in the control group. Mean operative time of LESS cholecystectomy group and LC group was 55.6 ± 25.7 versus 42.7 ± 18.6 ( p < 0.05). Mean postoperative hospital stay was 3.7 ± 1.3 versus 3.8 ± 0.8 days ( p < 0.05). Mean pain index was 2.8 ± 0.6 versus 3.7 ± 1.1 (p < 0.05). A questionnaire revealed that the mean scores of satisfaction with the operation were 8.9 ± 0.7 versus 8.1 ± 1.5 (p < 0.05). LESS cholecystectomy is safe, feasible, minimally invasive, and cosmetic. It is a reasonable alternative to selective patients with uncomplicated cholelithiasis and PLG. But larger controlled studies are still needed.